THE EFFECTS OF EARTHQUAKE AND TSUNAMI LOADINGS ON STRUCTURAL BEHAVIOR OF REINFORCED CONCRETE BUILDING - Sutarja, Nyoman; Pringgana, Gede; Santi Wikrama, Made Ari (Journal of Applied Engineering Science, 2021)
This study evaluates the effect of earthquake and tsunami loads on structural behavior of reinforced concrete building with varying heights. The purpose of this study is to evaluates the level of resilience of building structures that are designed to withstand earthquake loads when loaded by tsunami loads. Building structure behavior is evaluated based on the amount of internal forces, displacements and drift ratio. In making models of building structures with varying heights where the plans are planned on their own. The building structure model is planned to be resistant to earthquake loads where the evaluation is carried out on the comparison of static earthquake loads with dynamic earthquake loads and the drift ratio between building floors meets the limits permitted by SNI-1726-2012. Furthermore, the same structural model is loaded with tsunami loads which refers to FEMA P646 in 2012. The magnitude of the planned tsunami load is adjusted to the building height variations, which are buildings 3, 5 and 7 floors. The loading done on the building is earthquake load, combination tsunami load 1 (T1) and combination tsunami load 2 (T2). The results are obtained in the 3-story building structure, the drift ratio due to earthquake load, T1 and T2 still meet the inter-floor permit drift ratio. The maximum drift ratio value on the first floor of a 3-storey building structure due to earthquake loads, T1 and T2 are 0.75%, 0.52% and 1.01%, respectively, which are all smaller than the limits of the drift ratio of buildings categorized as risk IV which is 1%. In the structure of buildings 5 and 7 floors, the value of the drift ratio on the first floor due to earthquake load still meets the requirements (
Keywords: earthquake loads, tsunami loads, internal forces, drift, drift ratio